IMPLEMENTASI PEMBELAJARAN ILMU TAJWID DALAM MENINGKAT KEMAMPUAN MEMBACA AL-QUR’AN - Sinta Nur Khofifah, Sinta Nur; Astutik, Anita Puji (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2024)
This research is an effort to implement recitation learning to improve the ability to read the Qur'an in students in class. Apart from being one of the pillars of Islam, the Al-Qur'an is a source of reference for law, life and so on, it is also the main study for every Islamic boarding school. The general aim of the existence of Islamic boarding schools is actually only to spread the flag of Islam and educate the younger generation of Islam more optimally because of the residence of a student. The science of tajwid and the Al-Qur'an become an inseparable unit, where the Al-Qur'an is read then the science of tajwid is used. Therefore, the law is to practice fardu ain because fatal errors can occur and even damage the rules of the Qur'an if one mispronounces the Qur'an. The methods used are varied so as to trigger students' enthusiasm for learning and exploring the mu'alimah's creativity. The problem in this research is how to implement the learning of Tajweed science at the Fadllillah Islamic Boarding School, and what are the supports and obstacles to the implementation of Tajwid science learning at School. This research includes qualitative research using the Fadllillah observation, interviews and documentation methods. Islamic Boarding